PENGARUH PEMBERIAN JUS PEPAYA TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI RT/RW 02/05 KELURAHAN PONDOK KACANG TIMUR TAHUN 2016 - Retno Sri Yulianti (Jurnal Kesehatan STIKes IMC Bintaro, 2017)
Hypertension is a big challange for a doctor in Indonesia. Person who has uncontrol hypertension will cause some dangerous disease even death. Based on data result at Pondok Kacang Timur RT/RT 002/05, Pondok Aren, South Tangerang In 2016, is found 25,8% hypertensive patients. One of handling which has been done a lot is high potassium intake. Papaya is a food source of potassium. The purpose of this study was to determine the effect of papaya juice on the decrease in blood pressure in hypertensive patients in RT/RW 02/05 Pondok Kacang Timur. This type of research is quantitative with quasy experimental pre and post test with non equivalent control group design, conducted on 36 patients with hypertension. The result showed that there was a significant influence between blood pressure before and after papaya juice administration with statistical test result using paired t-test of 0.000 < 0,05. Recommendation in this research is, for papaya juice can be applied to society to control hypertension.